Studi Studi Pengaruh Tingkat Getaran Tanah (Ground Vibration) Akibat Peledakan Terhadap Bangunan sekitar Pit 13 HW - Vandrianus Felix Feto Nuwa; Revia Oktaviani; Harjuni Hasan; Tommy Trides; Albertus Juvensius Pontus (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2023)
PT. PAMA is a company engaged in mining and is a contractor of PT. Indominco Mandiri which has been running since 1996. The work contract given is blasting, from blasting activities many impacts arise, one of which is ground vibration, therefore it is necessary to measure the level of ground vibration in the west block area where there are several critical areas in the form of buildings such as offices , solar (fuel oil) storage, and PT. Indominco Mandiri, where there have been complaints regarding large vibrations and the potential for diesel spills from fuel oil. In the study the peak vector sum (pvs) value produced in December 2022 was 1.57 mm/s with the closest distance of 785 meters and in January 2023 4.21 mm/s with a distance of 500 meters. The maximum use of explosives item for explosive holes in December 2022 and January 2023 is 2,513 kg. This pvs value is still safe, because it is still below 5.0 mm/s and according to SNI 7572: 2010.